1998
DOI: 10.1016/s0006-3495(98)77574-5
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Formation of Cubic Phases in Phosphatidylethanolamine Dispersions

Abstract: By means of x-ray diffraction we show that several sodium salts and the disaccharides sucrose and trehalose strongly accelerate the formation of cubic phases in phosphatidylethanolamine (PE) dispersions upon temperature cycling through the lamellar liquid crystalline-inverted hexagonal (Lalpha-HII) phase transition. Ethylene glycol does not have such an effect. The degree of acceleration increases with the solute concentration. Such an acceleration has been observed for dielaidoyl PE (DEPE), dihexadecyl PE, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
53
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 52 publications
14
53
1
Order By: Relevance
“…The contribution of such a cubic phase was shown to depend widely on the thermal history of the lipid sample, and the corresponding diffraction peaks were not detected in the present set of experiments [22].…”
Section: Discussioncontrasting
confidence: 62%
“…The contribution of such a cubic phase was shown to depend widely on the thermal history of the lipid sample, and the corresponding diffraction peaks were not detected in the present set of experiments [22].…”
Section: Discussioncontrasting
confidence: 62%
“…Relatively low lipid contents of 10% (w/v) were used to eliminate restricted volume effects and to ensure sufficiently large aqueous spaces in the lipid dispersions necessary for the development, in particular, of cubic lipid phases (23). Another reason to use low lipid contents was to ensure better compatibility of the x-ray results with the data on the stability of LUV prepared from the same lipid extracts.…”
Section: Luv Properties At High Naclmentioning
confidence: 99%
“…by PEs are for the most part less attractive as potential crystallization media than MGs, however, since they require rather extreme thermal cycling 21,24 or the inclusion of fusogenic additives 22,25 to form a wellequilibrated gel. However, we have found that a polyethyleneglycol derivative of PE (mPEG 550 PE; Avanti Polar Lipids, Inc., Alabaster, AL) is easily hydrated and forms a stiff gel that gives several orders of x-ray diffraction rings (Figure 7).…”
Section: Figurementioning
confidence: 99%